High Grade Endometrial Stromal Sarcoma: a rare case report - Rai, Snigdha (Nepal Journal of Obstetrics and Gynaecology, 2021)
High grade endometrial stromal sarcoma (HG-ESS) is a very rare entity with poor outcome in compared to other endometrial stromal sarcoma as it is usually diagnosed in late stage. The stage of the disease, age and complete surgery are most important prognostic factors. Surgical management of a 40 years old lady with menometrorrhagia and high grade endometrial stromal sarcoma is presented.